Features of polarization switching in printed films of polyvinylidene fluoride and its copolymer of poly(vinylidene fluoride-trifluoroethylene) - Alexander V. Solnyshkin; Nikita V. Vostrov; Sergey I. Gudkov (Modern Electronic Materials)
The paper studies the processes of spontaneous polarization switching in PVDF and P(VDF-TrFE) polymer films produced by 4D printing. The samples were synthesized by the direct ink writing technology. It was found that polarization reversal in PVDF samples is not observed in alternating fields less than 70 MV/m, and in P(VDF-TrFE) samples – in fields less than 35 MV/m. This phenomenon is associated, firstly, with the large mass of the objects being repolarized, which is determined by the mass of the entire polymer chain, and, secondly, with a strong dipole-dipole interaction between adjacent polymer chains of the crystalline phase of the polymer. An increase in the electric field above the specified values leads to a sharp increase in the residual polarization values and the appearance of saturated dielectric hysteresis loops. The coercive field of the P(VDF-TrFE) copolymer films is two times smaller than the corresponding value for PVDF films (38 and 80 MV/m, respectively). At the same time, the residual polarization value for the copolymer films is slightly lower than for PVDF films (30 and 35 μC/m2, respectively). The hysteresis loops were modeled according to the Preisach model. This model is based on the assumption that all lamellar crystals in the polymer have the same spontaneous polarization, each crystal has its own value of the coercive field and a rectangular dielectric hysteresis loop. The simulation showed that the average coercive field of the lamellar crystals of the PVDF polymer film is 91 MV/m, and for the P(VDF-TrFE) copolymer sample – 46 MV/m. The dispersion characterizing the distributions of the coercive and internal fields has a value of 16 MV/m for the PVDF polymer and 14 MV/m for the P(VDF-TrFE) copolymer.